Conference on Lasers and Electro-Optics 2017
DOI: 10.1364/cleo_qels.2017.ftu1d.2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soliton crystals in optical microresonators

Abstract: Dissipative Kerr solitons in optical microresonators provide a unifying framework for nonlinear optical physics with photonic-integrated technologies and have recently been employed in a wide range of applications from coherent communications to astrophysical spectrometer calibration. Dissipative Kerr solitons can form a rich variety of stable states, ranging from breathers to multiplesoliton formations, among which, the recently discovered soliton crystals stand out. They represent temporally-ordered ensemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 50 publications
4
63
0
Order By: Relevance
“…Previous works 23 , 45 have shown that soliton generation occurs in a certain range of the normalized pump detunings ζ , with the lower boundary being above the bistability criterion and the upper boundary being the soliton existence criterion: where is the normalized pump amplitude, ω 0 is the resonance frequency, c is the speed of light, n 2 is the microresonator nonlinear index, P in is the input pump power, n is the refractive index of the microresonator mode, V eff is the effective mode volume, κ is the loaded resonance linewidth, and η is the coupling efficiency ( η = 1/2 for critical coupling). Note, however, that the lower boundary (bistability) includes also a region of breather existence for high pump power 47 , so actual soliton region starts at a bit higher detunings. The linear SIL model 44 predicts that, in the SIL regime, the attainable detuning range of in the locked state does not overlap with the soliton existence range despite the sufficient pump power.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works 23 , 45 have shown that soliton generation occurs in a certain range of the normalized pump detunings ζ , with the lower boundary being above the bistability criterion and the upper boundary being the soliton existence criterion: where is the normalized pump amplitude, ω 0 is the resonance frequency, c is the speed of light, n 2 is the microresonator nonlinear index, P in is the input pump power, n is the refractive index of the microresonator mode, V eff is the effective mode volume, κ is the loaded resonance linewidth, and η is the coupling efficiency ( η = 1/2 for critical coupling). Note, however, that the lower boundary (bistability) includes also a region of breather existence for high pump power 47 , so actual soliton region starts at a bit higher detunings. The linear SIL model 44 predicts that, in the SIL regime, the attainable detuning range of in the locked state does not overlap with the soliton existence range despite the sufficient pump power.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a powerful category of micro-comb -soliton crystals -has attracted interest due to their crystallike profile in the angular domain in micro-ring resonators [17,[81][82][83]. They have underpinned breakthroughs in microwave and RF photonics [15,50], ultrahigh bandwidth communications [17] and optical neuromorphic processing [5].…”
Section: Soliton Crystal Micro-combsmentioning
confidence: 99%
“…Recently, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] microcombs have attracted significant interest as a fundamentally powerful tool for microwave processing, due to their ability to offer a large number of coherent wavelengths from a single device, thereby increasing the capacity of communications systems [40][41][42], for example. Further, they have enabled the processing of RF spectra for a wide range of advanced signal processing functions as well as neural networks [69][70][71].…”
Section: Introductionmentioning
confidence: 99%